1994
DOI: 10.1002/1520-6629(199404)22:2<97::aid-jcop2290220206>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Mental health of Asian Indians: Relevant issues and community implications

Abstract: The current body of research on Asian–American mental health issues has not sufficiently addressed the needs of Asian Indians. Demographically and historically this group is distinct from other Asian immigrant groups. This article examines how the unique aspects of Asian Indian culture may differentially impinge on mental health issues such as acculturation, rates of psychopathology, and manifestation of psychiatric symptoms. The ramifications of these factors for the construction of community mental health mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 31 publications
0
47
0
Order By: Relevance
“…In Indian culture, a strong attachment and sense of responsibility to the family form the very core of the culture (Durvasula and Mylvaganam 1994;Saran and Eames 1980). The traditional family structure of India has typically been patriarchal, hierarchical, extended, and interdependent (Das and Kemp 1997).…”
Section: Cultural Values and Beliefs Among Asian Indiansmentioning
confidence: 99%
See 1 more Smart Citation
“…In Indian culture, a strong attachment and sense of responsibility to the family form the very core of the culture (Durvasula and Mylvaganam 1994;Saran and Eames 1980). The traditional family structure of India has typically been patriarchal, hierarchical, extended, and interdependent (Das and Kemp 1997).…”
Section: Cultural Values and Beliefs Among Asian Indiansmentioning
confidence: 99%
“…The traditional family structure of India has typically been patriarchal, hierarchical, extended, and interdependent (Das and Kemp 1997). Family harmony and interdependence are highly encouraged among Indian families (Durvasula and Mylvaganam 1994). Children (regardless of gender) are expected to bring honor to the family by respecting elders, obeying authority figures without question, and adhering to cultural values (Durvasula and Mylvaganam 1994;Ranganath and Ranganath;Segal 1998).…”
Section: Cultural Values and Beliefs Among Asian Indiansmentioning
confidence: 99%
“…Researchers also discussed the feelings of stigma and shame attached to mental illness (Durvasula and Mylaganam 1994;Gilbert et al 2004). This is largely due to the misconception that mental illness is incurable.…”
Section: Mental Health Depression and South Asiansmentioning
confidence: 99%
“…Immigration to the United States opened up to professional and educated Indians in 1965 with the passing of the Immigration Act of 1965 (Durvasula & Mylvaganam, 1994;Quddus, 2005;Prashad, 2000). Acculturation may have been even more difficult for these immigrants as members of a collectivist culture of origin (Wong & Wong, 2006;Durvasula & Mylvaganam, 1994).…”
Section: Indian Diaspora In the United States And Collective Identitymentioning
confidence: 99%
“…Acculturation may have been even more difficult for these immigrants as members of a collectivist culture of origin (Wong & Wong, 2006;Durvasula & Mylvaganam, 1994). After a literature review, Bhugra (2005) concluded that migrants who move from a collectivistic culture to an individualistic one, where there is little social support, experience increased stress.…”
Section: Indian Diaspora In the United States And Collective Identitymentioning
confidence: 99%